Compensation of Voltage Single-Phase SAG and SWELL Using Dynamic Voltage Restorer and Difference Per-Unit Value Method - Mohammad Sarvi; Haniyeh Marefatjou (Institute of Advanced Engineering and Science, 2013)
Recently, the demand for high power quality by customers, has increased significantly. Common power equipment to protect sensitive loads against voltage disturbances in distribution networks, which are known by D-FACTS devices include: D-STATCOM , DVR and UPQC. Consequences resulting from industrial processes can be classified into two categories that are, nonlinear and unbalanced loads and high vulnerability to transient faults (such as voltage sag) in distribution systems. DVR is a equipment which was connected in series and adjusting the loading voltage by feeding the voltage in system. The first installation was in 1996. usually DVR installed between sensitive loads feeder and source in distribution system. The main duty, fast support load voltage (by fast detection algorithm) during disturbance to avoid any disconnection. In this paper approaches to compensate for voltage sag and swell as a common disturbance in voltage transmission and distribution networks is presented. A dynamic voltage restorer based on the average detection method for single-phase is discussed, in the other hand this paper describes the effect to using DVR inorder to restoring the voltage sag and swell by difference per-unit value method(average detection) in distribution system. The result of single-phase voltage sag and swell simulation has been presented by SIMULINK/ MATLAB.DOI:http://dx.doi.org/10.11591/ijece.v3i1.2134